Discovery of miRNAs and Development of Heat-Responsive miRNA-SSR Markers for Characterization of Wheat Germplasm for Terminal Heat Tolerance Breeding - Sihag, Pooja; Sagwal, Vijeta; Kumar, Anuj; Balyan, Priyanka; Mir, Reyazul Rouf; Dhankher, Om Parkash; Kumar, Upendra (Frontiers in Genetics, 2021)
Large proportion of the Asian population fulfils their energy requirements from wheat (Triticum aestivum L.). Wheat quality and yield are critically affected by the terminal heat stress across the globe. It affects approx. 40% of the wheat cultivating regions of the world. Therefore, there is a critical need to develop improved terminal heat tolerant wheat varieties. Marker assisted breeding with genic SSR (simple sequence repeats) markers have been used for developing terminal heat tolerant wheat varieties; however, only few studies involved the use of miRNA based SSR markers (miRNA-SSRs) in wheat, which were found as key players in various abiotic stresses. In the present study, we identified 104 heat stress responsive miRNAs reported in various crops. Out of these, 70 miRNA-SSR markers have been validated on a set of 20 terminal heat tolerant and susceptible wheat genotypes. Among these, only 19 miRNA-SSR markers were found to be polymorphic, which were further used to study the genetic diversity and population structure. The polymorphic miRNA-SSRs amplified 61 SSR loci with an average of 2.9 alleles per locus. The polymorphic information content (PIC) value of polymorphic miRNA-SSRs ranged from 0.10-0.87 with mean value of 0.48. The dendrogram constructed using unweighted neighbour joining method and population structure analysis clustered these 20 wheat genotypes into three clusters. The target genes of these miRNAs are involved either directly or indirectly in providing tolerance to heat stress. Further, two polymorphic markers miR159c and miR165b were declared as very promising diagnostic markers since these markers showed specific alleles and discriminated terminal heat tolerant genotypes from the susceptible genotypes. Thus, these identified miRNA-SSR markers will prove useful in characterization of wheat germplasm through the study of genetic diversity, population structural analysis and in wheat molecular breeding programs aimed at terminal heat tolerance of wheat varieties.